Dual soluble epoxide hydrolase inhibitor – farnesoid X receptor agonist interventional treatment attenuates renal inflammation and fibrosis - Khan, Md. Abdul Hye; Nolan, Benjamin; Stavniichuk, Anna; Merk, Daniel; Imig, John D. (Frontiers in Immunology, 2024)
Introduction: Renal fibrosis associated with inflammation is a critical pathophysiological event in chronic kidney disease (CKD). We have developed DM509 which acts concurrently as a farnesoid X receptor agonist and a soluble epoxide hydrolase inhibitor and investigated DM509 efficacy as an interventional treatment using the unilateral ureteral obstruction (UUO) mouse model. Methods: Male mice went through either UUO or sham surgery. Interventional DM509 treatment (10mg/kg/d) was started three days after UUO induction and continued for 7 days. Plasma and kidney tissue were collected at the end of the experimental protocol. Results: UUO mice demonstrated marked renal fibrosis with higher kidney hydroxyproline content and collagen positive area. Interventional DM509 treatment reduced hydroxyproline content by 41% and collagen positive area by 65%. Renal inflammation was evident in UUO mice with elevated MCP-1, CD45-positive immune cell positive infiltration, and profibrotic inflammatory gene expression. DM509 treatment reduced renal inflammation in UUO mice. Renal fibrosis in UUO was associated with epithelial-to-mesenchymal transition (EMT) and DM509 treatment reduced EMT. UUO mice also had tubular epithelial barrier injury with increased renal KIM-1, NGAL expression. DM509 reduced tubular injury markers by 25-50% and maintained tubular epithelial integrity in UUO mice. Vascular inflammation was evident in UUO mice with 9 to 20-fold higher ICAM and VCAM gene expression which was reduced by 40-50% with DM509 treatment. Peritubular vascular density was reduced by 35% in UUO mice and DM509 prevented vascular loss. Discussion: Interventional treatment with DM509 reduced renal fibrosis and inflammation in UUO mice demonstrating that DM509 is a promising drug that combats renal epithelial and vascular pathological events associated with progression of CKD.